Second to fourth digit ratio (2D:4D) and concentrations of circulating sex hormones in adulthood - Morris Howard A; Bassett Julie; Giles Graham G; Muller David C; Manning John T; Hopper John L; English Dallas R; Severi Gianluca (BMC, 2011)
Abstract Background The second to fourth digit ratio (2D:4D) is used as a marker of prenatal sex hormone exposure. The objective of this study was to examine whether circulating concentrations of sex hormones and SHBG measured in adulthood was associated with 2D:4D. Methods This analysis was based on a random sample from the Melbourne Collaborative Cohort Study. The sample consisted of of 1036 men and 620 post-menopausal women aged between 39 and 70 at the time of blood draw. Concentrations of circulating sex hormones were measured from plasma collected at baseline (1990-1994), while digit length was measured from hand photocopies taken during a recent follow-up (2003-2009). The outcome measures were circulating concentrations of testosterone, oestradiol, dehydroepiandrosterone sulphate, androstenedione, Sex Hormone Binding Globulin, androstenediol glucoronide for men only and oestrone sulphate for women only. Free testosterone and oestradiol were estimated using standard formulae derived empirically. Predicted geometric mean hormone concentrations (for tertiles of 2D:4D) and conditional correlation coefficients (for continuous 2D:4D) were obtained using mixed effects linear regression models. Results No strong associations were observed between 2D:4D measures and circulating concentrations of hormones for men or women. For males, right 2D:4D was weakly inversely associated with circulating testosterone (predicted geometric mean testosterone was 15.9 and 15.0 nmol/L for the lowest and highest tertiles of male right 2D:4D respectively (P-trend = 0.04). There was a similar weak association between male right 2D:4D and the ratio of testosterone to oestradiol. These associations were not evident in analyses of continuous 2D:4D. Conclusions There were no strong associations between any adult circulating concentration of sex hormone or SHGB and 2D:4D. These results contribute to the growing body of evidence indicating that 2D:4D is unrelated to adult sex hormone concentrations.